Police Omnipresence Program and Practices: Views of Police Officers in Cebu City - Delposo, Baltazar; Sabijon, Dodelon (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study explored the views of police officers regarding Police Omnipresence Programs and Practices in Cebu City, Cebu, Philippines. Anchored on the Routine Activity Theory of Cohen & Felson (1979), supported by the Broken Windows Theory of Wilson & Kelling (1982) and the Deterrence Theory of Becker (1968), the study examined police officers’ experiences, perceived impacts, challenges, and aspirations related to police omnipresence implementation. The research employed a qualitative transcendental phenomenological design following Moustakas (1994). Data were gathered through individual in-depth interviews and focus group discussions using a validated interview guide. Ten Philippine National Police patrol officers assigned to the Police Omnipresence Program and with at least two years of patrol experience were selected through purposive sampling. Data were analyzed using Colaizzi’s (1978) method. Findings revealed that police omnipresence positively contributed to public safety, crime deterrence, and stronger police-community relations through visible police presence and active community engagement. Officers reported that visible policing increased public trust, encouraged community cooperation, and enhanced their professional growth, communication skills, and interpersonal expertise. However, challenges such as limited personnel, inadequate equipment, operational strain, insufficient coverage, and lack of recognition negatively affected implementation and officer morale. Informants also emphasized the importance of stronger collaboration with stakeholders, efficient personnel deployment, improved communication systems, and enhanced operational planning to strengthen the sustainability and effectiveness of the program. The study concluded that police omnipresence remains an important strategy for crime prevention and public reassurance but requires adequate resources, strengthened partnerships, and community-oriented policing approaches to improve operational efficiency and public trust. The study supports Sustainable Development Goal (SDG) 16 on Peace, Justice, and Strong Institutions by promoting effective law enforcement and safer communities, as well as SDG 11 on Sustainable Cities and Communities through proactive public safety initiatives. The study contributes to institutional, governance, and community sustainability by promoting collaborative crime prevention, public confidence, and long-term social cohesion.